O constitucionalismo contemporâneo ante a virada hermenêutico-linguística: aplicações ao direito processual civil - Macedo, Lorena Neves (2014)
The present research intents to investigate contemporary constitucionalism against the influence that it has suffered from de hermeneutic-linguistic turn, which proposes a disruption with the paradigm of metaphysics, extending the analysis of influence to the civil procedural law and applying quickly some findings to this juridical province. For that, initially approaches the historical evolution from modernity to postmodernity, collating it, in sequence, that with the historical evolution of constitucionalism, as well as considering democratic ambient as necessary condition for the consolidation of contemporary constitucionalism. Works, sequentially, the passage from the metaphysical subjectivity, connected with modernity, to the postmetaphysical intersubjectivity, currently stimulated in a certain way by postmodernity and with the development of linguistic philosophy, wich can be considered as the phenomenom of the linguistic turn. Considers, in sequence, the close relation between law and language and the notorious influence that law theory has suffered against the linguistic turn phenomenom. Identifies, in this purpose, as highlighting two heritages to be worked under perspective of law, being the first one the analisis of legislation under perspective of semiotics of power and the second one the analisis of interpretation by law applicator, with what it considers the principals manifestation of law incompleteness, wich are the indeterminate legal concepts and the fundamental constitucional principles. Considers, then, historical evolution of civil procedure law, taking in count its phase and current chains of comprehension, accomplishing notes about the close relation between procedure and language and about the applicability of linguistic turn phenomenon. Works, then, the two mentioned heritages of linguistic turn connected to civil procedure: the analisis of semiotics of power against procedural legislation and the analisis of indeterminate legal concepts and fundamental principles and how occurs is construction, now obligatory by the civil procedural legislation, about everything beyond the paradigmatic heritages already evidenced.